2005
DOI: 10.1210/jc.2004-2132
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Receptors 7 and 8 Are Expressed in Human Adrenocortical Cells, and Their Endogenous Ligands Neuropeptides B and W Enhance Cortisol Secretion by Activating Adenylate Cyclase- and Phospholipase C-Dependent Signaling Cascades

Abstract: Neuropeptides B and W (NPB and NPW) are regulatory peptides that act via two subtypes of G protein-coupled receptors, named GPR7 and GPR8. RT-PCR demonstrated the expression of these receptors in both zona glomerulosa and zona fasciculata-reticularis (ZF/R) cells of the human adrenal cortex. NPB and NPW did not affect aldosterone secretion from dispersed zona glomerulosa cells but enhanced cortisol production from ZF/R cells, NPB being more effective than NPW. NPB evoked sizable cAMP and inositol triphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 35 publications
(38 reference statements)
5
41
0
Order By: Relevance
“…The expression of both NPB and NPW and their receptors in the adrenal cortex confirms earlier findings obtained in the rat (14) and human adrenocortical cells (17,27). These studies showed that both peptides stimulate in vitro glucocorticoid secretion from dispersed or cultured cells, and our present in vivo RIA observations agree with this contention.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of both NPB and NPW and their receptors in the adrenal cortex confirms earlier findings obtained in the rat (14) and human adrenocortical cells (17,27). These studies showed that both peptides stimulate in vitro glucocorticoid secretion from dispersed or cultured cells, and our present in vivo RIA observations agree with this contention.…”
Section: Discussionsupporting
confidence: 92%
“…As demonstrated, NPB activates and binds to both human NPBWR1 (with higher affinity) and NPBWR2, and similar effects are demonstrated with NPW23 and NPW30, with NPBWR1 binding with lower affinity (6,8). Previous observations revealed notable differences in NPB and NPW action on both rat and human adrenocortical cells (18,20,24). Present data on leptin and insulin regulation by NPB and NPW extend these earlier observations to include differences in the biological activity of both neuropeptides.…”
Section: Discussionsupporting
confidence: 82%
“…Concerning the functional role of the NPB-NPW system, a growing body of evidence indicates that this system is involved in the regulation of neuroendocrine axis activity. This suggestion is confirmed by findings demonstrating that NPB or NPW evoked secretion of anterior pituitary and adrenocortical hormones in vivo (5,10,18,20,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…cAMP and IP3 production. In the case of cAMP assay, the phosphodiesterase inhibitor IBMX (10 -4 M) was added to prevent cAMP metabolism (23). cAMP was extracted by incubating the medium with 0.1 N HCl for 20 min at 4˚C.…”
Section: Gal-r Immuno-blockadementioning
confidence: 99%